2012
DOI: 10.1002/app.36663
|View full text |Cite
|
Sign up to set email alerts
|

Composites from northern red oak (Quercus robur) leaves and plant oil‐based resins

Abstract: Composite materials were successfully made out of plant oil-based resin and northern red oak (Quercus robur) leaves collected in the fall. The viscosities of the bio-based resins (MAESO and MAELO) were suited to high temperature resin transfer molding (RTM) and vacuum-assisted resin transfer molding (VARTM) processing. The leaves have a waxy epidermal surface layer that needs to be dewaxed prior to use in a composite part. We used different treatments (such as benzene-ethanol, boiling water, and strong deterge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…In addition, the piles of leaves also create a potential fire hazard that can damage hundreds of hectares of woods annually, and release gases as well as large plumes of black smoke and other contaminants into the atmosphere. It was reported that in the United States some 30 million tons of leaves are collected and burned every year [17].…”
mentioning
confidence: 99%
“…In addition, the piles of leaves also create a potential fire hazard that can damage hundreds of hectares of woods annually, and release gases as well as large plumes of black smoke and other contaminants into the atmosphere. It was reported that in the United States some 30 million tons of leaves are collected and burned every year [17].…”
mentioning
confidence: 99%
“…Fresh leaf yields of 40 ton/ha/year (nearly 10 tons of dry matter) have been reported for some species in Costa Rica (Espinoza et al 1999). In the forest, leaves fall on to the ground and can be both beneficial (become food for numerous soil organisms vital to the forest ecosystem (Campanella et al 2013) or detrimental [ignition point in wildfires (Ozkaya et al 2013) and soil metal concentration concerns (Heckman and Kluchinski 1996). Foliage biomass, fuel depth, fuel bulk density, and foliage retention are of important indices in prediction of fire behavior properties in forests (Bilgili 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Foliage biomass, fuel depth, fuel bulk density, and foliage retention are of important indices in prediction of fire behavior properties in forests (Bilgili 2003). In cities and towns, leaves are predominantly considered a waste; they are collected and burned and in rare cases are composted (Campanella et al 2013) and in villages usually are used by farmers as a ruminant roughage source for cows (Ozkaya et al 2013). Only in the United States, there are 30 million tons of leaves that are collected and burned every year (Campanella et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations